2022
DOI: 10.1007/s40333-022-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-negligible factors in low-pressure sprinkler irrigation: droplet impact angle and shear stress

Abstract: Droplet shear stress is considered as an important indicator that reflects soil erosion in sprinkler irrigation more accurately than kinetic energy, and the effect of droplet impact angle on the shear stress cannot be ignored. In this study, radial distribution of droplet impact angles, velocities, and shear stresses were investigated using a two-dimensional video disdrometer with three types of low-pressure sprinkler (Nelson D3000, R3000, and Komet KPT) under two operating pressures (103 and 138 kPa) and thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
3
1
1
Order By: Relevance
“…Water 2024, 16, x FOR PEER REVIEW 10 of 15 In addition, it is important to note from the regression analysis that droplet shear stresses and impact angles under three slopes and two directions had obvious exponential relationships, which could be expressed by = e d s S c  . These results do not coincide with the polynomial relationship between the two indicators obtained by Hui et al [33] using a low-pressure sprinkler on flat land. This also implies a stronger regularity between these two indicators under the influence of the slope, and it could be observed from Table 2 that the average R 2 value under various treatments was 0.879.…”
Section: Relationship Between Droplet Impact Angle and Shear Stress O...contrasting
confidence: 93%
See 4 more Smart Citations
“…Water 2024, 16, x FOR PEER REVIEW 10 of 15 In addition, it is important to note from the regression analysis that droplet shear stresses and impact angles under three slopes and two directions had obvious exponential relationships, which could be expressed by = e d s S c  . These results do not coincide with the polynomial relationship between the two indicators obtained by Hui et al [33] using a low-pressure sprinkler on flat land. This also implies a stronger regularity between these two indicators under the influence of the slope, and it could be observed from Table 2 that the average R 2 value under various treatments was 0.879.…”
Section: Relationship Between Droplet Impact Angle and Shear Stress O...contrasting
confidence: 93%
“…In addition, it was not difficult to find that the farther distance from the sprinkler on sloping land was associated with a more dispersed droplet impact angle, which suggested that the spray jet end might also be the area where droplets collided most violently with each other. This result is consistent with the droplet diameter distributions obtained by Hui et al [21] using a ball-driven sprinkler and Hui et al [33] using low-pressure sprinklers. Furthermore, it can be observed from Figure 4 that the droplet impact angle distribution varies with slope and direction.…”
Section: Radial Droplet Impact Angle Distribution On Sloping Landsupporting
confidence: 92%
See 3 more Smart Citations